The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1143/jjap.44.6230
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Ion Mobilities and their Effects on Gas Discharge of AC Plasma Display Cells

Abstract: We have found that ion mobilities in a gas mixture greatly affect discharge characteristics of a plasma display cell. Therefore, correct ion mobilities are required to obtain meaningful simulation results on plasma display cells. Since plasma display panels use microdischarges in the Xe mixed gas to generate vacuum ultraviolet light to excite phosphor for visible light emission, the condition of the discharge gas mixtures is one of the main factors that determine luminous efficacy. Thus, intensive studies on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…t f is usually considered to be mainly affected by the electric field applied across the discharge space and by the discharge gas species, since t f does not significantly depend on exoelectron emission when the discharge is triggered by one priming electron more than a few hundreds of s after the previous discharge, 8) where exoelectrons are priming sources of the discharge. Therefore, the correlations between t f and other factors, such as accumulated charges, 9) temperature, 10,11) electric field, 10,11) wall charge leakage, 10,11) and discharge gas composition, 12) have been intensively investigated. However, taking into account that exoelectron emission is affected by various parameters, such as temperature, electric field and gas species, and causes charge leakage, it is strongly suggested that exoelectron emission affects t f as well.…”
Section: Introductionmentioning
confidence: 99%
“…t f is usually considered to be mainly affected by the electric field applied across the discharge space and by the discharge gas species, since t f does not significantly depend on exoelectron emission when the discharge is triggered by one priming electron more than a few hundreds of s after the previous discharge, 8) where exoelectrons are priming sources of the discharge. Therefore, the correlations between t f and other factors, such as accumulated charges, 9) temperature, 10,11) electric field, 10,11) wall charge leakage, 10,11) and discharge gas composition, 12) have been intensively investigated. However, taking into account that exoelectron emission is affected by various parameters, such as temperature, electric field and gas species, and causes charge leakage, it is strongly suggested that exoelectron emission affects t f as well.…”
Section: Introductionmentioning
confidence: 99%